Quality assurance and assessment practices in translation and interpreting - Huertas-Barros, Elsa, 1984-; Vandepitte, Sonia; Iglesias-Fernandez, Emilia, 1966- (Information Science Reference, 2018)
"This book focuses on the behavior and good assessment practices of both translation and interpreting practitioners and educators, which will provide trainees with information about industry assessment practices and will also inform the way translation and interpreting trainees should be trained"--